The Role of Chatgpt and Generative Artificial Intelligence in Shaping the Future of Islamic Teacher's Effectiveness in Southern Pakistan - Majeed, Muhammad Kashif; Ahmad, Tunku Badariah (Jurnal Penelitian Agama, 2025)
A Generative Artificial Intelligence (AI) technology like ChatGPT is becoming an effective asset in changing how people worldwide study in the new age of the fast-paced technological revolution. Nevertheless, its translation to pedagogy in rural and religious settings is poorly investigated. This paper examines the use of ChatGPT and generative AI to improve teacher effectiveness in secondary schools in the region of Southern Pakistan and on gender-based analyses. Even though the concept of AI-based education has become an item of interest to the entire world, there is a significant research gap in the application of AI in the classroom, the preparedness of the instructional staff, and gender disparities in under-resourced education settings in, such as Kot Addu. This will be determined by research that seeks to (1) establish the level of ChatGPT and AI adoption among teachers in Islamic secondary schools, (2) how generative AI is affecting teacher effectiveness, lesson planning, and student interaction, and (3) the differences in the perceptions and application of these tools by male or female teachers. A structured questionnaire was further used in a quantitative method of research administered to a group of 440 Islamic secondary school teachers in the Kot Addu District. The analysis of the data was performed using the SPSS 2021, where descriptive statistics, t-test, and correlation analysis were used. The most significant results demonstrate average rates of AI integration, which positively impact instructional innovation and teacher-student interaction. It's interesting to note that there were gender differences, with male teachers using the generative AI tools more actively and with a little more confidence than their female counterparts. In order to empower all educators, the research article highlights the necessity of inclusive digital policies and targeted training activities. These findings have practical ramifications for education executives and policymakers who wish to bridge the digital divide in the context of Islamic education in southern Pakistan.